Evaluasi Organoleptik Multinutrien Blok yang dibuat dengan Menggunakan Metode Dingin pada Perbedaan Aras Molases: Organoleptic Evaluation of Multinutrient Block Processed by the Cold Methods on Different Level of Mollases (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
This research aimed to evaluated and assessed the effect of the molasses level on organoleptic quality of multinutrient block (MnB). The materials used were corn forage, bentonite, urea, salt, molasses, water, blood clamshell and egg shells. The experimental designed used was a Completely Randomized Design with  4 treatments (T0 = MnB Formulation T0 + 0% of molasses, T1 = MnB Formulation T1 + 20% of molasses, T2 = MnB Formulation T2 + 35% of molases, and T3 = MnB Formulation T3 + 50% of molasses) and 4 replications. The variables observed were moisture content, texture, colored and aroma of MnB. The results showed that the addition of molasses had significantly (P